2015
DOI: 10.1038/onc.2015.159
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of vacuolar ATPase subunit in tumor cells delays tumor growth by decreasing the essential macrophage population in the tumor microenvironment

Abstract: In cancer cells, vacuolar ATPase (V-ATPase), a multi-subunit enzyme, is expressed on the plasma as well as vesicular membranes and critically influences metastatic behavior. The soluble, cleaved N-terminal domain of V-ATPase a2 isoform is associated with in vitro induction of tumorigenic characteristics in macrophages. This activity led us to further investigate its in vivo role in cancer progression by inhibition of a2 isoform (a2V) in tumor cells and the concomitant effect on tumor microenvironment in the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
58
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 28 publications
0
58
0
Order By: Relevance
“…For example, a soluble cleavage fragment of V o a2 (a2NTD) has been shown to polarize macrophages toward a “tumor‐associated” or M2 macrophage phenotype 40, 69…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…For example, a soluble cleavage fragment of V o a2 (a2NTD) has been shown to polarize macrophages toward a “tumor‐associated” or M2 macrophage phenotype 40, 69…”
Section: V‐atpase Function In Cancer Cellsmentioning
confidence: 99%
“…Important initiators that mediate the interaction between tumor cells and leukocytes are the vacuolar ATPases (V-ATPases); that are highly expressed on cancer cell surface456789. V-ATPases are novel targets for anticancer therapeutics45.…”
mentioning
confidence: 99%
“…Our previous studies have shown that specifically the a2-isoform of the ‘a’ subunit of V-ATPase (a2V) plays a significant role in the inflammation associated with cancer and pregnancy82122. In cancer cells, a2V is highly expressed on the plasma membrane and the N-terminal domain of a2V (a2NTD) is secreted in microvesicles68921. a2NTD stimulates M2 polarization of the macrophages, which behave as TAM and have a positive impact on tumor progression168.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the lysosomal adaptor protein Lamtor1, which forms an amino-acid sensing complex with V-ATPase, was recently shown to be required for M2 polarization [55]. Moreover, V-ATPase was reported to modulate macrophage polarization in tumor-bearing mice [56], and inhibition of the V-ATPase a2 isoform in murine tumor cells delayed tumor growth by decreasing M2-like TAMs in the tumor microenvironment [57].…”
mentioning
confidence: 99%